2012
DOI: 10.1631/jzus.b1100356
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium accumulation in different pakchoi cultivars and screening for pollution-safe cultivars

Abstract: Abstract:The selection and breeding of pollution-safe cultivars (PSCs) is a practicable and cost-effective approach to minimize the influx of heavy metal to the human food chain. In this study, both pot-culture and field experiments were conducted to identify and screen out cadmium pollution-safe cultivars (Cd-PSCs) from 50 pakchoi (Brassica rapa L. ssp. chinensis) cultivars for food safety. When treated with 1.0 or 2.5 mg/kg Cd, most of the pakchoi cultivars (>70%) showed greater or similar shoot biomass when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Edible plants are the predominant dietary source of cadmium for humans. More than 70% of our cadmium uptake comes from vegetables (Ryan and others ; Chen and others ). According to Chary and others (), cadmium has very high mobility and phyto‐availability and relatively poor adsorption in soils.…”
Section: Occurrence Of Toxic Elements In Foodstuffsmentioning
confidence: 99%
“…Edible plants are the predominant dietary source of cadmium for humans. More than 70% of our cadmium uptake comes from vegetables (Ryan and others ; Chen and others ). According to Chary and others (), cadmium has very high mobility and phyto‐availability and relatively poor adsorption in soils.…”
Section: Occurrence Of Toxic Elements In Foodstuffsmentioning
confidence: 99%
“…Two Cd accumulation contrasting cultivars of B. chinensis L. low; Aijiaoheiye 333 (AJ) and high; Zhouyeheiyoudonger (ZH) Cd accumulator cultivar (Chen et al, 2012), were used for the experiment. Sieved soil (2 kg) was placed in each (20 cm × 20 cm) plastic pots set on plastic saucers.…”
Section: Plant and Greenhouse Experimentsmentioning
confidence: 99%
“…chinensis) is an important leafy vegetable crop. Variability among pak choi cultivars in Cd accumulation has been reported 21 , 22 . Although several studies revealed that antioxidant enzymes play important roles in genotypic variation of Cd tolerance, understanding the antioxidative defense mechanisms in different pak choi cultivars is still unknown, especially at the molecular level.…”
Section: Introductionmentioning
confidence: 99%